Bioinspired Slippery Lubricant-Infused Surfaces With External Stimuli Responsive Wettability: A Mini Review - Yang, Xian; Huang, Yu; Zhao, Yan; Zhang, Xiaoyu; Wang, Jinhua; Sann, Ei Ei; Mon, Khin Hla; Lou, Xiaoding; Xia, Fan (Frontiers in Chemistry, 2019)
Responsive slippery lubricant-infused surfaces (SLIS) have attracted substantial attention because of the high demand of fundamental research and practical applications, such as controllable liquid-repellency, intelligent and easy-to-implement wettability switching. In this review, advanced development of responsive slippery surfaces is briefly summarized upon various external stimuli, including stress, electrical field, magnetic field, and temperature. In addition, remaining challenge and prospect are also discussed.